The Role of Local Cultural Traditions in Strengthening Community Identity: A Case Study of Village Rituals - Dhanny Septimawan Sutopo (Journal of Innovative and Creativity, 2025)
This study explores the significant role that local cultural traditions, particularly village rituals, play in strengthening community identity in an era of rapid globalization and cultural homogenization. Through a qualitative descriptive methodology utilizing library research, this research examines how traditional ceremonies and customs serve as essential mechanisms for preserving cultural heritage, fostering social cohesion, and reinforcing collective identity among community members. The study analyzes various dimensions of village rituals, including their historical evolution, symbolic significance, social functions, and contemporary adaptations. Findings indicate that village rituals operate as powerful instruments of cultural preservation and identity formation by creating shared experiences, reinforcing value systems, establishing intergenerational connections, and adapting to changing socio-economic conditions while maintaining their core cultural essence. This research contributes to our understanding of how local traditions can be sustained and leveraged as vital resources for community resilience and cultural distinctiveness in the face of modernizing influences. Keywords: Cultural traditions, community identity, village rituals, cultural preservation, social cohesion, collective memory, intergenerational transmission, cultural adaptation